Effect of nutrient management practices on yield and economics of pearl millet based intercropping systems under rainfed situations - Rawat, Bishan; Kamboj, Navish Kumar; Kumar, Ramesh; Gupta, Gaurendra (Annals of Agricultural Research, 2019)
The field investigation entitled, "Nutrient management in pearl millet based intercropping systems in rainfed situations" was conducted at CCS HAU Krishi Vigyan Kendra farm, Mahendergarh during Kharif 2011. The experiment comprised of 13 treatments viz., Pearl millet sole with recommended dose of nitrogen (RDN), Pearl millet + cluster bean and Pearl millet + mung bean intercropping each with 100 per cent nitrogen to main crop (M100) and 100 per cent N to intercrop (I100), M100 I0, M75 I100, M75 I0, M50 I100 and M0 I0 nitrogen levels. The experiment was conducted in randomized block design with three replications. Based on the research findings, it was found that cluster bean intercropping with pearl millet with 75 to 100 per cent nitrogen dose to main crop and 100 per cent nitrogen dose to intercrop produced statistically equal yields to sole pearl millet. The pearl millet equivalent yield of pearl millet + cluster bean intercropping with 100 per cent nitrogen dose to both the crops were significantly higher as compared to other intercropping treatments as well as sole crop of pearl millet.